A secret itinerary: surviving images in Paisagem com dromedário, by Carola Saavedra (Simbiótica. Revista Eletrônica, 2022)
The article focuses on the relationship between the images and the historical-cultural archive, and more specifically the literary one, based on Carola Saavedra's work Paisagem com dromedário. Bearing in mind a contemporary artistic trend of hybridization and reassembly of aesthetic elements, through which boundaries of identity determination are shaken, we seek here to reflect on the surviving forms of images in temporalities intercepted by a certain look at the present. To this end, theorizations around the archive in its relationship with the contemporary trace a peculiar itinerary posed by the field of experience and its forms of resistance. Paisagem com dromedário, a contemporary work, provides precious clues of these ghost-images scratching the archive, opening it up to other possibilities of exploration.Keywords: Archive; Surviving images; Contemporary; Paisagem com dromedário.